Determination of the 1% doramectin grace period in bovine tissues - Capanema Ribeiro, Rosanne Aparecida; Santos, Elaine Alves dos; Martins, Otavio Augusto [UNESP]; Raghiante, Fernanda (Univ Federal Ceara, Centro Ciencias Agrarias, 2020)
The present work aimed to determine the grace period for 1% doramectin in muscle, fat, kidney and liver of cattle applied at a concentration of 1%, subcutaneously, at a dose of 1 ml/50 Kg (200 mu g/kg) in cattle. Twenty animals were evaluated in the experiment, divided in five groups, each one containing four animals slaughtered at the moments of D+7 (group A), D+14 (group B), D+28 (group C), D+35 (group D) and D+42 (group E). The maximum residue limits established in Codex Alimentarius Commission for Doramectin in muscle, liver, fat and kidney, are 10 mu g/kg, 100 mu g/kg, 150 mu g/kg e 30 mu g/kg, respectively. After 28 days of the treatment, the results were below these values, therefore, according to the alternative approach for withdraw period stated in EMEA/CVMP/036/95 Final, the withdraw period determined for 1% doramectin was 31 days.
Keywords: Maximum residue limit; antiparasitic; public health